123k views
5 votes
Evaluate 32 + (6 − 2) ⋅ 4 − 6 over 3

2 Answers

2 votes

Answer:

14

Explanation:

32+(6-2)•4-6

32+4•4-6

32+16-6

48-6

42/3

14

User Shogunivar
by
5.7k points
7 votes

Answer:

88/3

Explanation:

Simplify the following:

32 + (6 - 2) (4 - 6)/3

(6 - 2) (4 - 6)/3 = ((6 - 2) (4 - 6))/3:

32 + ((6 - 2) (4 - 6))/3

4 - 6 = -2:

32 + ((6 - 2) -2)/3

6 - 2 = 4:

32 + (4 (-2))/3

4 (-2) = -8:

32 + (-8)/3

Put 32 - 8/3 over the common denominator 3. 32 - 8/3 = (3×32)/3 - 8/3:

(3×32)/3 - 8/3

3×32 = 96:

96/3 - 8/3

96/3 - 8/3 = (96 - 8)/3:

(96 - 8)/3

| 8 | 16

| 9 | 6

- | | 8

| 8 | 8:

Answer: 88/3

User Dhruvbird
by
5.8k points